Learning the Values of Religious Moderation in Madrasah Aliyah: Model Analysis - Zulfatmi, Zulfatmi (Jurnal Ilmiah Peuradeun, 2023)
Islamic religious education (PAI) teachers still need help in carrying out learning value that is integrated into learning at school or madrasah. However, implementing the 2013 curriculum emphasizes the importance of value integration in learning, including the values ​​of religious moderation, which can strengthen the value of national unity and integrity. This study presented a learning model for the value of moderation in religion in the Aqidah Akhlak subject at Madrasah Aliyah Aceh, focusing on the perspectives of students and teachers on the learning model for the value of moderation in religion which has so far been implemented and the readiness of teachers in lesson plan based on internalizing the value of religious moderation. The researchers obtained data on the perspectives of students and teachers regarding the learning model of religious moderation values taken from questionnaires and interviews. Data on religious moderation learning plans were a document review from two Madrasah Aliyah Negeri (MAN- Public Islamic Senior High School) 2 in Aceh Tamiang Regency and Madrasah Aliyah (MA) Ulumul Qur'an in Langsa, Indonesia. The applied values learning models have not been able to facilitate students to think critically, resolve value conflicts, and internalize values in students. It has affected students' awareness of applying the values of religious moderation in their lives. The learning plan and design of the religious moderation values in Madrasah Aliyah have not met the standards. Therefore, it remains a big task for educators to strive for better quality values education in formal education, especially in Madrasah Aliyah.